The impacts of trade liberalization on the mexican countryside: 24 years from the North American free trade agreement - Silva, Vanessa Gonçalves da; Cabral, José Pedro Cabrera (Seven Editora, 2024)
This text aims to contribute to the debate initiated in the 2000s by the BRICS initiative on Middle-Income Countries (MRCs) and the impacts of development cooperation policies. Based on the implementation of the 1994 North American Free Trade Agreement (NAFTA) between the United States, Canada and Mexico. It was presented at the time as a policy of development cooperation that later proved to be a large-scale action of expansion of North American market capitalism. The premise that guides the research was to analyze the socioeconomic impacts in the Mexican countryside with a focus on: a) the impacts on labor markets; (b) agricultural production and food security; c) internal and external migratory processes. The research was carried out from academic documentary sources, newspapers and official documents of the Mexican government. The focus of the analysis was a critical reading of the processes triggered by the implementation of NAFTA in the Mexican countryside. The results point to the following impacts: a) a significant increase in unemployment and informal work in the Mexican countryside; b) the increase in both internal and external migratory processes; c) the worsening of a food crisis unprecedented in the country's history. DOI:https://doi.org/10.56238/sevened2023.006-145